Intersecting pathways : modern Jewish theologians in conversation with Christianity - Krell, Marc A. (Marc Aaron), 1967- (American Academy of Religion cultural criticism series., 2003)
Marc A. Krell analyses the theologies of four 12th-century Jewish thinkers: Hans Joachim Schoeps, Franz Rosenzweig, Richard Rubenstein and Irving Greenberg, who have constructed theologies based on their interaction with Christian thought and culture.